Synthesis of a novel nanostructured zinc oxide/baghdadite coating on Mg alloy for biomedical application: In-vitro degradation behavior and antibacterial activities. Issue 17 (1st December 2017) - Bakhsheshi-Rad, H.R.; Hamzah, E.; Ismail, A.F.; Aziz, M.; Kasiri-Asgarani, M.; Akbari, E.; Jabbarzare, S.; Najafinezhad, A.; Hadisi, Z.
Abstract: In this research, zinc oxide (ZnO) and zinc oxide/baghdadite (ZnO/Ca3 ZrSi2 O9 ) were prepared on the surface of Mg alloy using physical vapor deposition (PVD) coupled with electrophoretic deposition (EPD). For this purpose, the nanostructured ZnO was prepared with a thickness of 900 nm and crystallite sizes of 64 nm as under layer while nanostructured baghdadite with a thickness of 10 µm was deposited on the Mg alloy substrate as an over-layer. Electrochemical measurement exhibited that the ZnO/Ca3 ZrSi2 O9 -coated specimen has a higher corrosion resistance and superior stability in simulated body fluid (SBF) solution in comparison with the ZnO-coated and bare Mg alloy samples. Antibacterial activities of the uncoated and coated specimens were evaluated against various pathogenic species ( Escherichia coli, Klebsiella pneumoniae, and Shigella dysenteriae ) via disc diffusion method. The obtained results showed that ZnO and ZnO/Ca3 ZrSi2 O9 coatings have great zones of inhibition (ZOI) against E. coli, Klebsiella, and Shigella . However, less ZOI was found around the bare Mg alloy. Therefore, ZnO/Ca3 ZrSi2 O9 is a promising coating for orthopedic applications of biodegradable Mg alloys considering its excellent antibacterial activities and high corrosion resistance.